Pendidikan Holistik dalam Pengembangan Karakter Siswa - Sriyanta, Sriyanta; Mujahid, Kasori; Suranto, Muh. (Lembaga Yasin AlSys, 2025)
Holistic education is an educational approach that builds humans as a whole by developing all the potential that exists in humans. Holistic education aims to shape the character and personality of students, not only intellectually but also spiritually, morally, and socially. With the active role of teachers and the environment, holistic education can help develop the potential of individuals to become whole humans. Holistic education has advantages and disadvantages, but with collaborative efforts between educational institutions, teachers, parents, and the community, holistic education can shape individuals who are balanced and have strong characters.